Hepatitis B and D Virus Co-Infection: A Study of Seroprevalence and IgM Response among Patients in Abakaliki Metropolis, Ebonyi State, Nigeria - Azibanyam, Okosigha Saviour; Kenneth, Imarenezor Edobor Peter; Ifeoma, Anyiam Vivian (African Journal of Medicine, Surgery and Public Health Research, 2025)
Hepatitis, an inflammation of the liver commonly caused by viral infections, exists in five primary forms: Hepatitis A, B, C, D, and E. Among these, Hepatitis D virus (HDV) is a defective virus that requires co-infection with Hepatitis B virus (HBV) for replication. Hepatitis may present as acute or chronic, and early diagnosis and treatment are essential to prevent complications. This study investigated the seroprevalence of HBV and HDV co-infection among patients in Abakaliki Metropolis, Ebonyi State, Nigeria. A cross-sectional analytical design was employed, involving 1,000 patients who attended the Federal Teaching Hospital Abakaliki (FETHA) and Mile 4 Hospital Ishieke. Serological testing was conducted using ELISA kits in accordance with the manufacturer’s protocols and standard laboratory procedures. Of the 1,000 participants, 89 (8.9%) tested positive for HBsAg, indicating HBV infection, while 5 (5.6%) of these were also positive for HDV-IgM, confirming co-infection. The prevalence of HBV/HDV co-infection was higher among females (7.7%) compared to males (2.7%) and more pronounced among married individuals (6.9%) than singles (3.2%). These findings indicate a notable burden of HBV and HDV co-infection in the study area. The results underscore the importance of routine HDV screening for all HBsAg-positive patients and the implementation of targeted public health interventions to prevent HDV transmission and reduce the severity of HBV-related disease.